2018
DOI: 10.29252/jirss.17.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Bayes, E-Bayes and Robust Bayes Premium Estimation and Prediction under the Squared Log Error Loss Function

Abstract: In risk analysis based on Bayesian framework, premium calculation requires specification of a prior distribution for the risk parameter in the heterogeneous portfolio. When the prior knowledge is vague, the E-Bayesian and robust Bayesian analysis can be used to handle the uncertainty in specifying the prior distribution by considering a class of priors instead of a single prior. In this paper, we study the E-Bayes and robust Bayes premium estimation and prediction in exponential model under the squared log err… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The AUC of a classifier is equivalent to the likelihood that the classifier will rank a randomly selected positive value higher than a randomly selected negative value [ 26 ]. Log loss is also essentially used as a metric for classification; it is calculated by the probability of actual and predicted classes [ 27 ]. Log loss is among the most useful evaluation metrics.…”
Section: Methodsmentioning
confidence: 99%
“…The AUC of a classifier is equivalent to the likelihood that the classifier will rank a randomly selected positive value higher than a randomly selected negative value [ 26 ]. Log loss is also essentially used as a metric for classification; it is calculated by the probability of actual and predicted classes [ 27 ]. Log loss is among the most useful evaluation metrics.…”
Section: Methodsmentioning
confidence: 99%
“…Three attributes of the three loss functions (MSE, LogSE, and MSLE) are studied and compared in Table 2. The mean squared logarithmic error (MSLE) [Kiapour 2018, Brown 1968] is defined as the mean over the squared differences between the logarithm of real and estimated values. Actually, it measures the ratio between the true and predicted values.…”
Section: Methodsmentioning
confidence: 99%
“…Considering that the prior information may be deficient, the E-Bayesian method could be used to settle the uncertainty by introducing a class of priors. The authors in [14] demonstrated that, based on a specified prior distribution, the purpose of the E-Bayesian method is to estimate unknown parameters or to predict values of a sequence of random variables.…”
Section: E-bayesian Estimationmentioning
confidence: 99%